Alam membentuk identitas nasional di tengah keberagaman - Najwah, Felline (Maliki Interdisciplinary Journal, 2025)
Multicultural education plays a vital role in shaping national identity, particularly in countries with high levels of diversity such as Indonesia. Through an inclusive approach that respects cultural differences, multicultural education serves as a means to instill national values, tolerance, and unity within a plural society. Thus, education functions not only as a transfer of knowledge but also as a tool for character building that upholds unity in diversity. In the context of ethnic, religious, and cultural diversity, multicultural education provides space for individuals to recognize and appreciate both their own identity and that of others. This fosters a collective awareness that differences are not obstacles, but assets that enrich national identity. An educational process that emphasizes intercultural dialogue and cross-cultural understanding can strengthen social solidarity and promote harmonious national integration. By integrating multicultural values into the curriculum, school-based learning can help shape a young generation that is proud of their nation and open to diversity. Therefore, multicultural education is not only relevant in addressing the challenges of globalization but also serves as a cultural strategy to reinforce the nation’s identity. Effective implementation of multicultural education is key to forming an inclusive and sustainable national identity. Keywords: multicultural education, national identity, diversity, tolerance, social integration. Pendidikan multikultural memiliki peran penting dalam membentuk identitas nasional, terutama di negara yang memiliki tingkat keberagaman tinggi seperti Indonesia. Melalui pendekatan yang inklusif dan menghargai perbedaan budaya, pendidikan multikultural mampu menjadi sarana untuk menanamkan nilai-nilai kebangsaan, toleransi, dan kesatuan di tengah masyarakat yang plural. Dengan demikian, pendidikan tidak hanya berfungsi sebagai transfer ilmu, tetapi juga sebagai alat pembentukan karakter bangsa yang menjunjung tinggi persatuan dalam perbedaan. Dalam konteks keberagaman etnis, agama, dan budaya, pendidikan multikultural memberikan ruang bagi setiap individu untuk mengenali dan menghargai identitas dirinya serta identitas orang lain. Hal ini menciptakan kesadaran kolektif bahwa perbedaan bukanlah penghalang, melainkan kekayaan yang memperkaya identitas nasional. Proses pendidikan yang mengedepankan dialog antarbudaya dan pemahaman lintas budaya dapat memperkuat solidaritas sosial dan mendorong integrasi nasional secara harmonis. Melalui integrasi nilai-nilai multikultural dalam kurikulum, pembelajaran di sekolah mampu membentuk generasi muda yang memiliki rasa bangga terhadap bangsa serta sikap terbuka terhadap keberagaman. Kata kunci: pendidikan multikultural, identitas nasional, keberagaman, toleransi, integrasi sosial.